Performance and Outcome of Pioneering Kidney Transplantation in a Resource-Constrained Setting in Southeast Nigeria - Okwuonu, C G; Achor, G O; Erondu, N M; Ekwenna, O; Alhassan, S; Abali, C; Okam, E; Ralph-Iheke, C; Ngwu, P; Chukwuonye, I I; Onyebuchi, A; Balogun, R A (West African journal of medicine, 2025)
Kidney transplantation is the optimal treatment for improving survival and quality of life for patients with end-stage kidney disease. There was no kidney transplant surgery and acute transplant care services in Southeast Nigeria until 2017 when our institution commenced kidney transplant surgery and acute transplant care. This study aims to share our first eight year experience including graft and patient outcome. To obtain the transplant rate, short and long term complications and the graft and patient survival over an eight year period in a tertiary hospital in Southeast Nigeria. A retrospective review of the transplant register for patients referred to the kidney transplant unit over an eight year period from January 2017 to January 2025. Complete data for ninety-three patients were analyzed. Out of these, twelve were transplanted giving a transplantion rate of 13%. Financial constraint is the leading reason (40%) for failure to get a kidney transplant done. Hypertension, hyperkalemia, anemia and urinary tract infection were the leading acute complications encountered while cytomegalovirus infection, recurrence of native disease, chronic graft loss and death were the major long term complications. The three-month, one-year, three-year and five-year patient survival in our program were 100%, 90%, 80% and 80% respectively while the graft survival were 90%, 90%, 70% and 60% respectively. The transplant conversion rate is low and a review of atient selection criteria will improve access kidney transplant. Acute complications were treatable in most cases. The patient and graft outcomes appear similar with other centres in Nigeria.